In Situ Fe and S isotope analyses in pyrite from the 3.2 Ga Mendon Formation (Barberton Greenstone Belt, South Africa): Evidence for early microbial iron reduction. Issue 3 (2nd March 2020) - Marin‐Carbonne, Johanna; Busigny, Vincent; Miot, Jennyfer; Rollion‐Bard, Claire; Muller, Elodie; Drabon, Nadja; Jacob, Damien; Pont, Sylvain; Robyr, Martin; Bontognali, Tomaso R. R.; François, Camille; Reynaud, Stephanie; et al.
Abstract: On the basis of phylogenetic studies and laboratory cultures, it has been proposed that the ability of microbes to metabolize iron has emerged prior to the Archaea/Bacteria split. However, no unambiguous geochemical data supporting this claim have been put forward in rocks older than 2.7–2.5 giga years (Gyr). In the present work, we report in situ Fe and S isotope composition of pyrite from 3.28‐ to 3.26‐Gyr‐old cherts from the upper Mendon Formation, South Africa. We identified three populations of microscopic pyrites showing a wide range of Fe isotope compositions, which cluster around two δ 56 Fe values of −1.8‰ and +1‰. These three pyrite groups can also be distinguished based on the pyrite crystallinity and the S isotope mass‐independent signatures. One pyrite group displays poorly crystallized pyrite minerals with positive Δ 33 S values > +3‰, while the other groups display more variable and closer to 0‰ Δ 33 S values with recrystallized pyrite rims. It is worth to note that all the pyrite groups display positive Δ 33 S values in the pyrite core and similar trace element compositions. We therefore suggest that two of the pyrite groups have experienced late fluid circulations that have led to partial recrystallization and dilution of S isotope mass‐independent signature but not modification of the Fe isotope record. Considering the mineralogy and geochemistry of the pyrites and associated organic material, we conclude that this iron isotope systematic derives from microbial respiration of iron oxides during early diagenesis. Our data extend the geological record of dissimilatory iron reduction (DIR) back more than 560 million years (Myr) and confirm that micro‐organisms closely related to the last common ancestor had the ability to reduce Fe(III).